PULAU PANAS PERKOTAAN AKIBAT PERUBAHAN TATA GUNA DAN PENUTUP LAHAN DI BANDUNG DAN BOGOR - Laras Tursilowati (Jurnal Sains Dirgantara, 2005)
Urban development can affect climate element change, especially in downtown which is different from the surrounding, known as "Urban Heat Island (UHI)" phenomena. In this research we investigate air temperature changes on the land use and land cover by using case study in Bandung and Bogor on 1994 and 2001. We use the LANDSAT data of TM5 and ETM7 with spatial resolution of 30m x 30m, climate data from 1970-2003, and land use data from 1994-2003. The results shows that land cover causing the increase of temperature, i.e. residence, industry, and open land, were spreading. Consequently, UHI spreading over those area. Percentage of land use for residential area in Bogol was 11.3%, large than in Bandung (5.39%). Contrarily, larid cover causing the decrease of air temperature, i.e. high vagetation area (forest), seasonal plant, plantation, water badies, were decreasing. From the both investigated area, forest is decreasing, in Bogor the decrease 32.37% and Bandung 26.64%. Along with the changes of land use andland cover, so do air temperature changes. The increase of area related with air temperature in Bogor was 29.56% for temperature range (24-28)℃, while in Bandung was 21.79% for temperature range (24-29)℃. Area in Bandung having highest air temperature that increase was those with air temperature (28-29)℃, while in Bogor was those with air temperature (27-28)℃.